Study of dielectric and physiochemical propertiesof soil at Bastar region of India (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In the upcoming awareness for different soil types and its impact on various physical, chemicalproperties and holding capacity, it is critical to investigate the impact of inorganic materials onsoil dielectric potential at microwave frequencies. In this regard, different soil specimens weregathered from varioussites of Dantewada district around NMDC Dantewada agricultural land(Villages- Kirandul, Bade- Bacheli, Bacheli,Bhanshi). Surprisingly, not much has been reportedtowards the chemical propertiesof the key constituents of these different soils. In the presentstudy, we therefore investigated the different properties of soils, particularly to the dielectricpotential from different locations, at microwave frequency. The data revealed the sensitivitytowards various soil types and thus helped in determining the soil texture. Furthermore, byknowing the electrical conductivity and dielectric potential of soil samples, various chemicalparameters including the different percentages of clay, slit and different physical properties werethus explored.These findings concluded that at different locations, there is remarkable variationin physical and chemical properties of soils. Also, the observed values of soil dielectriccharacteristics are in good accord with previous research. As a result, researchers working in thefield of agriculture might benefit from these characteristics.